Serum fibroblastic growth factor 23 in acute Sarcoidosis and normal kidney function - Sexton, Donal J; O'Reilly, M. W.; Geoghegan, P.; Kinsella, S.M.; Moran, P.J.; O'Regan, A.W. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: Serum fibroblastic growth factor (FGF) 23 has recently been established as a major physiological regulator of phosphate homeostasis and may have a causal role in adverse cardiovascular and bone outcomes. However its role in states of disordered phosphate homeostasis and normal kidney function is as yet under characterised. Aims: To investigate whether this biomarker of vascular calcification and adverse bone outcomes is detectable in patients with sarcoidosis. Design: We conducted a cross sectional study on a convenience sample of patients presenting with acute sarcoidosis to a respiratory tertiary referral unit. Methods: We set out to systematically examine the characteristics and determinants of serum FGF-23 in patients presenting with acute sarcoidosis. Results: We studied 39 patients, 26 were male. Mean (SD) age was 33 (9.6) years. 15.4% of patients had a serum level of FGF-23 ≥ 9.9 pg/mL. The remaining 84.6% of patients had a serum FGF-23 < 9.9 pg/mL. Those with a detectable serum FGF-23 had a significantly higher serum calcium (P = 0.007), and lower serum iPTH (P